PREPARING STUDENTS AS AGENTS OF SOCIAL CHANGE: ANTI-RACISM AND ANTI-ETHNOCENTRISM EDUCATION THROUGH A SOCIAL JUSTICE- BASED CURRICULUM - Sunnah Sunnah; Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the role of anti-racism and anti-ethnocentrism education within a social justice-based curriculum framework as an effort to prepare students to become agents of social change. The background of this study is based on the urgency of building critical awareness and inclusive attitudes amid increasing social challenges resulting from racial and ethnic discrimination. The method used is library research through a systematic review of academic literature, previous studies, educational policy documents, and examples of curriculum implementation in various contexts. The results of the study indicate that integrating anti-racism and anti-ethnocentrism values into the curriculum can strengthen students' social awareness, empathy, and critical thinking skills regarding issues of injustice. The success of implementation requires participatory learning strategies, support from competent teachers, and an inclusive school environment. This study recommends strengthening teacher training, selecting multicultural teaching materials, and formulating education policies that prioritise social justice to ensure the sustainability of positive impacts on society at large.